Il deposito e la fossa all’interno dell’edificio D: considerazioni sulle olle nei depositi votivi etruschi (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
This contribution focuses on two complete vases, a jar and a cup, found inside the votive deposit and the pit of building D. They were part of the same ritual equipment together with the deposition of bones of wild animals. This association of elements recalls other similar ones, which are here collected and contextualised in a direct relationship with buildings, structures and the divinities involved (Ati, Apa, Uni Xia), in order to point out similarities and differences. The overall characteristics of the Tarquinian deposit point to chthonian and liminal divine entities, such as Selvans, Thufltha.
Keywords: Tarquinia; Civita; building D; excavations by P. Romanelli; votive deposits with jars; Selvans; Thufltha; Ati; Apa